Synthesis, spectroscopy and photosensitizing properties of hydroxynitrophenylporphyrins - Maestrin,Ana Paula J. (2004)
The hydroxynitrophenylporphyrins, 5,10,15,20-tetrakis(2-hydroxy-5-nitrophenyl)porphyrin and 5-mono(carboxyphenyl)-10,15,20-tris(2-hydroxy-5-nitrophenyl)porphyrin described in this work were prepared through Adler's method. These compounds were characterized by ¹H NMR and light absorption and emission spectroscopy in the visible region. In order to demonstrate the involvement of ¹O2 production, the uric (UA) acid test was carried out, which considers the decrease in the absorbance of UA at 293 nm following laser light irradiation of a solution containing UA and a photosensitizer. The results obtained demonstrate that these hydroxynitrophenylporphyrins can be considered as promising photosensitizers in PDT.